Aplikátor termoplastŭ a jeho vyuzití ve stomatologické protetice - Kantor, J; Kantor, T; Svaton, J (Prakticke zubni lekarstvi, 1989)
The authors describe an apparatus of their own design for the melting and application of thermoplasts. They discuss its construction and possible use for the preparation of fixed and removable dentures.
Keywords: Denture, Partial, Fixed; zubní náhrady částečné fixní; vysoká teplota; Denture Design; Denture, Partial, Removable; zubní náhrady částečné snímatelné; návrh zubní protézy; Hot Temperature